2016
DOI: 10.1039/c5tb02567b
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and immuno-reactivity in mice induced by intramuscular implants of HSNGLPL peptide grafted-polyurethane

Abstract: Synthetic peptide-based polyurethanes (PUs), introduced as bioactive agents and possessing impressive properties, have emerged as attractive functional biomaterials for tissue regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…[29][30][31] We previously demonstrated that monocyte/ macrophage responses can be readily induced in the skeletal muscle of B6 mice that received the synthetic implants, 30,31 indicating that the recruitment of these cells into the muscle containing foreign implants is crucial for the subsequent inflammation response and muscle regeneration. Monocytes/macrophages are the most important players in this system.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] We previously demonstrated that monocyte/ macrophage responses can be readily induced in the skeletal muscle of B6 mice that received the synthetic implants, 30,31 indicating that the recruitment of these cells into the muscle containing foreign implants is crucial for the subsequent inflammation response and muscle regeneration. Monocytes/macrophages are the most important players in this system.…”
Section: Discussionmentioning
confidence: 99%
“…The degrading implants can cause myofiber degeneration that can be detected by H&E staining. 63 We did not notice any myofiber necrosis in the muscle tissue surrounding our samples, indicating that AS coating is nontoxic and does not cause a foreign body reaction. Structure of the myofibers was normal with well-defined nuclei at the implant interface as well as in the deeper layers of the muscle.…”
Section: Discussionmentioning
confidence: 51%
“…The N 1s peak intensity significantly increased after TGF‐β conjugated onto PCDU‐Peptide surface. Our previous report showed the N 1s peak intensity increases after the peptides were grafted onto the PU as pendent groups, since the nitrogen relative amounts in the peptide are higher than that in polyurethane . The N 1s peak intensity increase in Figure may also be attributed to the TGF‐β conjugated on PCDU‐peptide surface, because the factor has higher compositional N elements in its molecule than that of PCDU‐peptide.…”
Section: Resultsmentioning
confidence: 86%
“…In our previous work, we have reported the synthesis of PU with the pendent HSNGLPL peptide groups and the presenting of the characteristic absorption bands of the polymer by FTIR, XPS, and 1 H‐NMR spectra . Here, we further compared the XPS spectra of PCDU‐Peptide film with and without conjugating TGF‐β showing elements changes after the growth factor's affinity binding.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation